Measuring product-level export quality: Evidence from Asian motor vehicles sector - Andrey A. Gnidchenko (FIW - Research Centre International Economics, 2018)
We provide the combination of the Asian automotive trade case study and the analysis of indicators that may potentially reflect product quality. We try to assess the relevance of different indicators (particularly, weighted unit value, number of export lines, market share, Grubel-Lloyd index and relative net exports) for constructing an unbiased quality measure. We conclude that one should simultaneously use most indicators from the list to eliminate the impact of possible shocks on quality estimations.
Keywords: F14; F10; L62; L15; 330; quality; products; unit value; trade; diversification; motor vehicles; Asia